Pre-employment exam analysis of a military company and its relation to oral health - Thaís Richter de Araújo; Dagmar de Paula Queluz (Universidade Estadual de Campinas, 2015)
Absenteeism is determined as an absence from work, resulting in the decrease of the company's production and, consequentially, causing profit reduction. The employer must follow closely the employees' quality of life, assuring that they perform all their tasks effectively. Dental health is directly connected to the employee's general health status and cannot be put aside when trying to assure complete physical and mental well being of an individual. Aim: To analyze preemployment exams of a military company in order to identify, among all the reasons for exclusion, dental problems that ultimately resulted prevented hiring of job applicants. Methods: Information was collected in 2008 from the dental files of the Health Department archives, which contained data referring to the candidates applying for a specific position and permitted and analytical study of the reasons for exclusion, based on the International Classification of Diseases (ICD-10). Results: 10.24% (720) of the candidates, from a total of 7,029, were excluded for dental reasons, namely dental cavitation, 2.8% (197), and pulpal and periapical diseases, 3.14% (221). Conclusions: Aside from being limited, the results of this study suggest that dental problems influence a great deal on the quality of life of employees that are able for work, and, that being said, should be managed closely to reduce absenteeism in the workplace.